Optimizing feed processing parameters and alternative ingredients for enhanced broiler performance and pellet quality - Minson, Carter Douglas (My University, 2025)
A sequence of experiments were conducted to optimize and evaluate effects of feed processing parameters and alternative ingredient use on broiler growth performance and pellet quality. When pelleting feed, several pellet mill factors influence the final quality of a pellet, and understanding their interactions is crucial to producing the highest quality product. Two experiments were conducted to determine the effect of conditioner retention time, conditioning temperature, and mixer added fat inclusion, on the final pellet durability of broiler feed. Exp. 1 analyzed the effects of conditioning temperature and conditioner retention time and Exp. 2 analyzed the effects of mixer added fat inclusion and conditioner retention time on pellet durability. Samples were obtained and pellet durability was measured using the modified tumble box pellet durability index (M-PDI; Exp. 1) and percent pellets surviving the New Holmen Pellet Tester (60 sec; H60-PDI; Exp. 1 & 2). Both experiments were analyzed using PROC GLIMMIX in SAS v. 9.4 (Cary, NC). In Exp. 1, increasing conditioner retention time from 30 to 90 seconds increased (linear, P < 0.001) M-PDI and H60-PDI. As conditioning temperature increased from 74 to 85℃, there was no difference in H60-PDI but M-PDI improved (P < 0.01).  In Exp. 2, there was a fat inclusion ´ conditioner retention time interaction (P = 0.019) for H60-PDI. Increasing conditioner retention time from 30 to 90 sec improved H60-PDI in diets containing 1.5 or 2% fat but not in diets containing 0.5 and 1.0% fat. Overall, these results emphasize the importance of better understanding the effects of changing pelleting process parameters and dietary fat inclusion levels have on pellet durability.   When altering processing parameters in feed manufacturing, it is imperative to assess the impact those changes can have on feed quality and broiler growth performance. Therefore, two experiments (Exp. 3 and 4) evaluated the effects of pellet die diameter and pellet fines inclusion on broiler growth performance. Exp. 3 used a 3 x 2 factorial design with 3 pellet die diameters (4.0 mm, 4.8 mm, and 6.4 mm) and 2 fines inclusions (0% and 30%) fed from d 12-47. Exp. 4 used as a 2 x 3 factorial with 2 pellet die diameters (4.8 mm and 6.4 mm) and 3 fines inclusions (0%, 30%, and 60%), fed from d 14-49, with a crumble (4.8 mm or 6.4 mm) being fed from d 0-14. Data were analyzed using PROC GLIMMIX in SAS v. 9.4 (Cary, NC). In Exp 3., overall growth interactions were observed for both FI (P = 0.015) and BWG (P = 0.013), where fines reduced performance in 4.0 and 4.8 mm pellet diets, but improved FI and BWG with 6.4 mm pellets. In Exp. 4, the 4.8 mm pellet die diameter, increased FI (P = 0.003), BWG (P < 0.001), and improved FCR (P = 0.002) in the starter phase. From d 0-49, increasing fines improved (linearly, P < 0.05) FCR, though no interactions were observed for FI and BWG. These results suggest that while increased fines generally impair broiler growth performance, their inclusion alongside a 6.4 mm pellet may help mitigate the typical negative impacts associated with higher pellet fines.  When implementing alternative ingredients into broiler diets, an ingredient in the process of being researched for its use as an alternative ingredient is CoverCress Whole Grain (CCWG). CCWG is a variety of pennycress with low erucic acid and reduced fiber content, was developed as a cover crop. It is designed to be planted in the fall following corn harvest and harvested in the spring before planting soybeans. The objective of this experiment was to determine the effect of including up to 6% CCWG seed in diets on broiler chicken growth performance over 49 days. Dietary treatments were established using a control basal diet fed over four feeding phases and treatments were allocated as additional inclusion of 2%, 4%, or 6% CCWG added to the diet. On d 12, 28, 39, and 49, birds and feeders were weighed to determine feed intake (FI), body weight gain (BWG), feed conversion ratio (FCR), and mortality corrected FCR (adj. FCR). At d 0-12, d 0-28, d 0-39, and d 0-49, birds performed below the Cobb 500 objectives for body weight gain, feed intake and feed conversion. For d 0-12, d 0-28, and d 0-39 increasing CCWG in the diet showed no effect on FI, BWG, FCR, or adj. FCR. For d 0-49, no differences were observed for FI, BWG or FCR. However, birds fed the 6% CCWG in the diet had poorer (P = 0.019) adjusted FCR as compared to broilers fed the 0 and 4% CCWG diets which may have been due to the 6% inclusion finisher diet being less nutrient dense as compared to the other treatments. In conclusion, CCWG can be safely included into broiler diets up to 6% inclusion through 49 days without negatively affecting BWG, FI, and FCR, and up to 4% inclusion to 49 days without negatively impacting adj. FCR.
Keywords: Feed processing; Broiler performance; Pellet quality